Effects of compaction pressure on the temperature distribution in bunker type silage silo - TAN, FULYA; KAYISOGLU, BIROL; OKUR, ERSEN (The Indian Journal of Animal Sciences, 2018)
The aim of the research has been to determine effects of compaction pressureon temperature distribution in the silage material in bunker silo.The pressure measurement systemdeveloped within the scope of this research was used to measure the pressure distribution in the silo. Hobo E-348-UA-002–08 model temperature sensors were also used for temperature measurements.The all sensors were positioned in the silo at predetermined points. Temperature and pressure values were recorded in a datalogger during ensiling, fermentation and after fermentation stages.The data collection system is based on a graphical programming language NI LabVIEW software and NI CompactDAQ hardware modules.Work machine having palette of which weight was 13700 kg has been used to compact of maize silage.The average temperature of silage in the silo was 23.35 °C during ensiling, 29.04 °C during fermentation and 23.45 °Cduring the after fermentation stage.The maximum pressure on the silage material was applied during storage with a mean value of 0.34 bar. The highest temperature and pressure wereon the line in thefront of the silo while the lowest temperature and pressure were in the close to the rear wall of the silo.The effect of compaction pressure applied during the ensiling stage also continued during the fermentation stage.It was determined that there is a relationship between the pressure applied to silage and temperature. Results showed that temperature in the silage has been increased with increasing compaction pressure.